2010
DOI: 10.1186/1471-227x-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute mercury poisoning: a case report

Abstract: BackgroundMercury poisoning can occur as a result of occupational hazard or suicide attempt. This article presents a 36-year-old case admitted to emergency department (ED) due to exposure to metallic mercury.Case PresentatıonA 36-year-old woman presented to the ED with a three-day history of abdominal pain, diarrhea and fever. One week ago her daughter had brought mercury in the liquid form from the school. She had put it on the heating stove. One day later, her 14-month old sister baby got fever and died befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 6 publications
0
17
0
5
Order By: Relevance
“…This can lead to pneumonia, adult respiratory distress syndrome, headache, nausea and vomiting and even death 3. A case in the USA reported that a family was exposed to mercury vapour as a consequence of home gold ore processing and despite aggressive medical management two of the eight patients affected died due to pulmonary failure 4…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to pneumonia, adult respiratory distress syndrome, headache, nausea and vomiting and even death 3. A case in the USA reported that a family was exposed to mercury vapour as a consequence of home gold ore processing and despite aggressive medical management two of the eight patients affected died due to pulmonary failure 4…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde de akut civa zehirlenmesini konu alan çok sayıda olgu sunumu bulunmaktadır. [3][4][5][6][7][8][9] Civa ile oluşan ciddi zehirlenmelerde sinir sistemi, böbrekler, solunum sistemi, immün sistem, deri ve mukozalar etkilenmektedir. 3,10 Civanın solunum yolu ile alınması sonucunda pulmoner ödem, bronş epitelinde erozyon, asidoz, koma ve ölüm görülebilmektedir.…”
Section: Civa Zehirlenmesi Olan Hastanınunclassified
“…Granül biçi-minde çinko ya da kükürt civa üzerine serpilerek, eldiven giyildikten sonra elle toplanmalı ve parça-cıklar ağzı kapalı torbalarda saklanmalıdır. [1][2][3][4][5][6][7][8][9][10] Zehirlenme durumunda yapılması gereken uygulamalar Refik Saydam Hıfzıssıhha Mektebi Müdülüğü tarafından hazırlanan kaynakta ayrın-tıları ile açıklanmaktadır. * Bu çalışmada, bir ilköğretim okulunda fen bilgisi dersinde laboratuvarda bulunan civa şişe-sinin kırılması sonucu arkadaşları ile birlikte zehirlenme belirtileri gösteren ve hastaneye iştah-sızlık, baş ve karın ağrısı, bulantı ve bulanık gör-me şikâyetleri ile getirilen 14 yaşındaki kız öğ-renci sunulmuştur.…”
Section: Civa Zehirlenmesi Olan Hastanınunclassified
See 1 more Smart Citation
“…Mercury (Hg) is a persistent and highly toxic element [1]. It can be emitted from natural and anthropogenic sources, largely as gaseous elemental mercury (GEM) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%